2017
DOI: 10.1007/s10290-017-0286-0
|View full text |Cite
|
Sign up to set email alerts
|

Shipment frequency of exporters and demand uncertainty

Abstract: Firms adjust to differences in market size and demand uncertainty by changing the frequency and size of their export shipments. In our inventory model, transportation costs and optimal shipment frequency are determined on the basis of demand as well as inventory and per shipments costs. Using a cross section of monthly firm-product-destination level French export data we confirm that firms adjust on both margins for market size. In a stochastic setting, firms adjust to increased uncertainty by reducing their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The notion that trade frictions have an important per shipment component is in line with a literature that documents systematic patterns in the size and frequency of international shipments (Kropf and Sauré 2014;Hornok and Koren 2015;Békés et al 2017). We contribute to this literature by linking these patterns to comparative advantage in the production of quality and by quantifying the effect of these frictions on cross-country income inequality.…”
supporting
confidence: 65%
“…The notion that trade frictions have an important per shipment component is in line with a literature that documents systematic patterns in the size and frequency of international shipments (Kropf and Sauré 2014;Hornok and Koren 2015;Békés et al 2017). We contribute to this literature by linking these patterns to comparative advantage in the production of quality and by quantifying the effect of these frictions on cross-country income inequality.…”
supporting
confidence: 65%
“…More broadly, our approach relates to the literature that departs from modelling trade costs taking the iceberg form (see for example Hummels and Skiba (2004) for evidence on transport costs accruing per unit or Friedt and Wilson (2020) for the endogenous nature of transport costs). Our results are also consistent with Békés et al (2017) who investigate the relationship between uncertainty and shipping behaviour.…”
Section: Introductionsupporting
confidence: 92%
“…An alternative channel through which pirate activity may affect trade and the choice of shipment mode is through uncertainty. Békés et al (2017) show that firms tend to send less frequent but larger shipments to more uncertain markets. Piracy increases uncertainty by increasing the probability of losing a ship at sea.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The main messages that come out of these papers is that, when timely delivery is important, firms tend to rely more on closer providers the higher is their products' restocking rate; resort more to air shipping the more volatile is the demand for their products and the lighter these products are; and co-agglomerate in the presence of vertical linkages. It has also been shown that exporters react to increased volatility by reducing their number of shipments (i.e., their frequency) and that this response is amplified by the time needed to serve the destination market from the origin country (Békés et al, 2013).…”
Section: Channels and Mechanismsmentioning
confidence: 99%